L’Importance de la Relation dans le Changement Thérapeutique: Un Problème en Quête d’une Response Empirique - Tetreau, Bernard P. (Canadian Journal of Counselling and Psychotherapy, 2012)
The lack of empirical support concerning the efficacy of the counsellor as a teacher of interpersonal skills is emphasized. Comparisons of this role of teacher with that of therapist, while complexifying the issue, also points to the need of questionning the necessity per se of the therapeutic relationship so as to better assess its relative importance. Analysis of conditions generally thought to be conducive to therapeutic change leads to the proposal that empirical research should focus on the bodily components of the experiencing process; the author and his students are currently working in this direction by trying to vary the degree of immediacy of the therapist's presence as independent variable, and by comparing, through physiological and perceptual indices, the relative influence of verbal and nonverbal contact.